Pathomorphological characteristics of the restructuring of pancreatic ductal system in chronic pancreatitis - Kovalenko I.S. (Морфологія, 2013)
Background. Processes that could precede the development of pancreatic ductal adenocarcinoma are not well understood. Objective. Pathomorphological characteristics of the structural remodeling of the ductal apparatus of pancreas in patients with chronic pancreatitis, considering features of the ductal hypertension, proliferative and apoptotic activity of ductal epithelium. Methods. Complex pathomorphological study of pancreatic biopsies of 16 patients with severe pancreatic fibrosis at a chronic pancreatitis was performed. 10 patients had signs of pancreatic duct dilation, confirmed by ultrasound diagnostic, while in other patients ductal hypertension was not accompanied with the duct dilation. Immunohistochemical markers Ki-67 and Caspase-3 were used to detect proliferative and apoptotic activity, respectively. Results. Main morphological changes were manifested as: the concentric periductal fibrosis and local stenosis, the dysplastic changes of ductal epithelium with low level of proliferative activity and caspase -3 expression (in patients with pancreatic duct dilation); the cystic dilation of small and medium-sized intralobular ducts with low levels of Ki-67 and caspase-3 expression (in patients with ductal hypertension, but without pancreatic duct dilation); pancreatic intraepithelial neoplasia (PanIN) is accompanied with the excessive nuclear Ki-67 expression and the low cytoplasmic caspase-3 levels. Conclusion. Structural remodeling of the pancreatic ductal system during chronic pancreatitis were not associated with rising of Ki-67 or Caspase-3 expression levels, unless in case of pancreatic intraepithelial neoplasia.